ANALYSIS OF NEW RECOMMENDATIONS OF BASEL COMMITTEE ON BANKING SUPERVISION - D. S. Mel’Nik (Russian Journal of Economics and Law)
Objective: determining and analyzing differences between the old and new recommendations of Basel committee on banking supervision. Methods: abstract-logical. Results: basing on evaluation of various researchers’ opinions in the studies area, as well as studying the methodology and norms elaborated in Basel I, ІІ и ІІІ, the new requirements are analyzed and summarized for banking capital according to Basel ІІІ provisions. The issues are interpreted of social-economic essence of banking capital. Special attention is paid to the issue of sufficiency of banking capital. Scientific novelty: positive and negative aspects are revealed of new recommendations of Basel committee on banking supervision. The author comes to the conclusion that, in spite the critics of new liquidity indicators, they will not significantly influence developing crediting in long-term prospect. Besides, the proposed grouping of the new requirements to banking capital is optimal – they are group by the extent of importance. Practical value: possibility to efficiently implement the new recommendations of Basel committee on banking supervision.